2004
DOI: 10.1038/sj.jea.7500360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between environmental tobacco smoke and urinary cotinine levels in passive smokers at their residence

Abstract: Studies of the health effects of environmental tobacco smoke (ETS) using measured air concentrations are subject to bias. Cotinine, a nicotine metabolite detected in urine, has been recommended as a quantitative measure of nicotine intake and thus as a marker for ETS exposure in humans. The aim of this study was to correlate home indoor ETS levels with passive smokers' urinary cotinine levels. The urinary cotinine concentrations of 57 non-smoking women who spend 419 h a day at home and the nicotine levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
3
14
0
1
Order By: Relevance
“…Air nicotine concentrations measured in the present study were comparable to concentrations that have been reported from a Dutch 17 and a US study, 18 but air nicotine concentrations in the homes of smokers who smoked more than five cigarettes daily (median 1.37 and 0.65 mg/m 3 ) were somewhat lower then concentrations that have been reported from a Korean study (median = 3.23 mg/m 3 for homes where six or more cigarettes were smoked daily) 19 and another US study (geometric mean = 0.66 mg/m 3 for homes without smoking restrictions). 20 Within the present study we also found differences in air nicotine concentrations between countries: median air nicotine concentrations in German homes were approximately twice as high as air nicotine concentrations in Dutch homes.…”
Section: Discussionsupporting
confidence: 80%
“…Air nicotine concentrations measured in the present study were comparable to concentrations that have been reported from a Dutch 17 and a US study, 18 but air nicotine concentrations in the homes of smokers who smoked more than five cigarettes daily (median 1.37 and 0.65 mg/m 3 ) were somewhat lower then concentrations that have been reported from a Korean study (median = 3.23 mg/m 3 for homes where six or more cigarettes were smoked daily) 19 and another US study (geometric mean = 0.66 mg/m 3 for homes without smoking restrictions). 20 Within the present study we also found differences in air nicotine concentrations between countries: median air nicotine concentrations in German homes were approximately twice as high as air nicotine concentrations in Dutch homes.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, 11 of 57 wheezing babies presented cotinine levels higher than 10 ng/mg-cr, while 2 normal children presented higher levels of cotinine ( p  = 0.023). In a study that correlated home indoor SHS levels with passive smokers' cotinine urinary levels in Seoul, Korea, the cotinine levels differed significantly ( p <0.001) among the following variables: no smoking inside the house, smoking on the veranda or outdoors and smoking indoors (26). In an additional study, Wakefield et al (27) reported that the urinary excretion of nicotine in the children of smoking mothers correlated with the number of cigarettes the mother smoked and her smoking habits and that non-smoking parents were associated with lower levels of nicotine in children.…”
Section: Discussionmentioning
confidence: 99%
“…With a lower limit of detection for the NicCheck I test of 200 ng/mL, a low-positive result represents either a very light smoker, e.g. less than five cigarettes a day, or an individual with significant ETS exposure [14,15]. Approximately 37.9% of North Carolina adults permit smoking in the home and 19.5% of women work in places where smoking is permitted in public areas [22].…”
Section: Discussionmentioning
confidence: 99%